Stem cell research in Latin America: Update, challenges and opportunities in a priority research area - Palma, Verónica (2015)
Stem cell research is attracting wide attention as a promising and fast-growing field in Latin America, as it is worldwide. Many countries in the region have defined Regenerative Medicine as a research priority and a focus of investment. This field generates not only opportunities but also regulatory, technical and operative challenges. In this review, scientists from Uruguay, Mexico, Chile, Brazil and Argentina provide their view on stem cell research in each of their countries. Despite country-specific characteristics, all countries share several issues such as regulatory challenges. Key initiatives of each country to promote stem cell research are also discussed. As a conclusion, it is clear that regional integration should be more emphasized and international collaboration, promoted.